Honeymind [compact disc] - Platt, Ben; Hemby, Natalie (Interscope, 2024)
The anticipated third album (and debut on Interscope Records) from musician and actor Ben Platt. Named for the "honeylike" state of being in love ("like all the jagged thoughts and fears and anxieties in my brain are slowly smoothed out, until my mind is coated with warmth and sweetness,") the album was Executive Produced by Dave Cobb (Chris Stapleton, Brandi Carlile), written with notable songwriters Hillary Lindsey, Natalie Hemby, and Alex Hope, and sees Ben exploring a more understated, folk-leaning sound.